GE_GERICHTE P/8697/2019 vom 11. Juli 2022 - GE Cour de justice (2022)
BRIGANDAGE;VOL(DROIT PÉNAL);LÉSION CORPORELLE SIMPLE;TENTATIVE(DROIT PÉNAL);MENACE(DROIT PÉNAL);DISPOSITIONS PÉNALES DE LA LCR;DISPOSITIONS PÉNALES DE LA LSTUP;DISPOSITIONS PÉNALES DE LA LARM;SURSIS À L'EXÉCUTION DE LA PEINE;PRONOSTIC | CP.140.al1.ch1; CP.22.al1cum; CP.123.ch1; CP.139.ch1; CP.180.al1; LCR.94; LCR.95; LArm.33; LStup.19.al1.letd; CP.47; CP.42.al1; CP.49